NOD-like receptors in innate immunity and inflammatory disease - Nunez, Gabriel (Henry Stewart Talks, 2009)
Signaling pathways involved in the recognition of microbes, Nod-like receptors (NLRs), Signaling pathways activated by NLRs, Microbial components sensed by NLRs, Nod1 and Nod2 signaling pathways, Nod2 and Crohn's disease, Interactions between TLRs and NLRs, The inflammasome, NLRs and the Inflammasome